Limited Immunohistochemistry Panel in Subclassification of Poorly Differentiated Non-Small Cell Lung Carcinoma in a Scarce Resource Setup - Fawad, Rabiya (International Journal of Pathology, 2019)
Background: With the emergence of targeted therapies for non-small cell lung carcinoma with different efficacy and toxicity, differentiating between adenocarcinoma and squamous cell carcinoma in lung biopsies has become essential. In cases of poorly differentiated non-small cell lung carcinoma standard haematoxylin and eosin stained morphology cannot confidently subtype the tumour as adenocarcinoma and squamous cell. In these cases, limited panel of immunohistochemical markers including TTF-1, CK7 and p63 may serve as a useful tool to specify the subtype of lung carcinoma in a resource limited setup. Objectives: The aim of this study is to see the expression of IHC markers TTF-1, CK7 and p63 in poorly differentiated NSCLC and its importance in subtyping NSCLC as ADC & SCC in lung biopsy specimens. Methods: It was a Cross sectional study, conducted at Department of Pathology, SZABMU, PIMS Islamabad for a period of 12 months (September 2015 to August 2016). A total of 51 lung biopsies with poorly differentiated NSCLC were further stained with the IHC markers TTF-1, CK 7 and p63. Statistical analysis was performed using SPSS Version 21.Results: The mean age was 59±14 years with a male to female ratio of 2:1. 26 males (51%) and 5 females (9.8%) out of the total 51 cases were smokers. 41.2% cases expressed positivity for TTF-1, 39.2% for p63 and 51% were positive for CK7 staining. 80.4% of cases were sub-typed as ADC and SCC by using this panel of immunomarkers. 19.6% of cases were categorized as poorly differentiated carcinoma.Conclusion: Limited panel of IHC markers comprising of TTF1, p63 and CK7 can subtype a substantial percentage (80.4%) of poorly differentiated NSCLC.